So, 2×4 – 3r? – 3r? + 6x – 2 = (x2 – 2)(2×2 – 3x + 1). Now, by splitting -3x, we factorise 2×2 – 3x + 1 as 27 and x = 1. Therefore

Question

So, 2×4 – 3r? – 3r? + 6x – 2 = (x2 – 2)(2×2 – 3x + 1).
Now, by splitting -3x, we factorise 2×2 – 3x + 1 as 27
and x = 1. Therefore, the zeroes of
are given by x =
✓ -√2.
and 1.
2
EXERCISE 2.3
1. Divide the polynomial p(x) by the polynomial g(x) and find
in each of the following:
(1) p(x) = r – 3x² + 5x – 3, g(x)= x2 – 2​

in progress 0
Julia 1 month 2021-08-12T13:30:03+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-08-12T13:31:20+00:00

    Answer:

    SRRY IDK

    Step-by-step explanation:

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )